IMPLIKASI SERTIFIKASI HALAL TERHADAP DAYA JUAL DAGING: Studi Kasus Pada Penjual Daging di Pasar Palapa, Brayan - Cania, Ema Saswita; Batubara, Chuzaimah (International Journal Mathla’ul Anwar of Halal Issues, 2024)
This study examines the implications of halal certification on the sales of meat in Palapa Market, Brayan, using a phenomenological approach and data triangulation. The findings indicate that halal certification significantly enhances consumer trust and boosts sales, with an observed increase of up to 20% in some vendors after certification. Consumer surveys reveal that 80% of respondents prefer buying meat from certified vendors, aligning with previous research indicating that halal certification is associated with higher perceived quality and safety. However, the study also identifies challenges in obtaining certification, particularly the high costs and complex procedures, which pose significant barriers for small-scale vendors. To address these issues, government intervention and supportive policies are essential, including subsidies and streamlined certification processes. Overall, halal certification not only meets consumer demands and improves market competitiveness but also contributes significantly to economic growth in the halal food sector.